The Difference in Academic Performance of Private and Public Elementary School Graduates - Hernando L. Bernal Jr.; Renz Chester Gumaru; Sammy T. Oleo (RIRAI Publisher, 2020)
The study is about the difference of Private and Public elementary school graduates. The type of elementary school in which a person graduated from is a factor that can affect their future academic performance; it can also be a factor for schools in choosing which student to accept in their community. It also test and shows the quality of the teachers in both types of school. The researchers conducted the study to verify if there was an actual difference on the academic performance of the graduates on each of the two types of elementary school. The researchers believe that the results of this study will be beneficial to a lot of people especially students and teachers. The researchers collected, compared, and interpret the grades of students of both public school graduates and private school graduates. The gathered data are test using different statistical tools and formulas. This study found out that there is a significant difference between public school graduates and private school graduates in terms of academic performance.